Legus discovery of a light echo around Supernova 2012aw - VanDyk, Schuyler D.; Grebel, Eva K. (The astrophysical journal, 2015)
We have discovered a luminous light echo around the normal Type II-Plateau Supernova (SN) 2012aw in Messier 95 (M95; NGC 3351), detected in images obtained approximately two years after explosion with the Wide Field Channel 3 on board the Hubble Space Telescope by the Legacy ExtraGalactic Ultraviolet Survey. The multi-band observations span from the near-ultraviolet through the optical (F275W, F336W, F438W, F555W, and F814W). The apparent brightness of the echo at the time was ∼21-22 mag in all of these bands. The echo appears circular, although less obviously as a ring, with an inhomogeneous surface brightness, in particular, a prominent enhanced brightness to the southeast. The SN itself was still detectable, particularly in the redder bands. We are able to model the light echo as the time-integrated SN light scattered off of diffuse interstellar dust in the SN environment. We have assumed that this dust is analogous to that in the Milky Way with . The SN light curves that we consider also include models of the unobserved early burst of light from the SN shock breakout. Our analysis of the echo suggests that the distance from the SN to the scattering dust elements along the echo is pc. The implied visual extinction for the echo-producing dust is consistent with estimates made previously from the SN itself. Finally, our estimate of the SN brightness in F814W is fainter than that measured for the red supergiant star at the precise SN location in pre-SN images, possibly indicating that the star has vanished and confirming it as the likely SN progenitor.
Gesehen am 07.07.2020